Understanding and Managing Public Organizations - RAINEY, Hal G. (Jossey-Bass Publishers, 1997)
Understanding and Managing Public Organizations provides a comprehensive analysis of research and practice on public organizations and management. In this fourth edition of his award-winning best seller, Hal Rainey reviews topics including organizational goals and performance, decision making and strategy, leadership, motivation, organizational structure and design, organizational change, and others. He analyzes effective and ineffective practices, with suggestions for managing contemporary and classic challenges in public organizations, and with illustrative vignettes and examples. Carefully revised and updated, this edition of Understanding and Managing Public Organizations extends previous editions with deeper coverage of collaboration and networks, public values, public service motivation, managerial strategy, performance assessment, innovation and organizational change, and recent trends in public sector management.